Maturity-Model for the Evaluation of Investments into IIoT (European Journal of Marketing and Economics, 2025)
The transition from the second industrial revolution (electrification) to the third industrial revolution (automation) was accompanied by a transformation of economy into a science with a powerful mathematic foundation. The methods developed do have some inaccuracies, such as the assumption that logical agents drive the market, an assumption that was realized to be a failure in the models not long ago. The models were developed in a transition phase, while the industrial revolution took place. The models are currently not mature enough to support companies in their investment strategies for the fourth industrial revolution, the age of digitalization and interconnectedness. The purpose of this study is to create a theoretical model for the process of creating a business case for the investment in technologies within the Industrial Internet of Things (IIoT).
Keywords: Maturity-Model for the Evaluation of Investments into IIoT